Factor Extraction and Bicluster Analysis on Halal Destinations in Lombok Island - Desy Komalasari; Mustika Hadijati; Nurul Fitriyani; Agus Kurnia (Jurnal Varian, 2020)
Indonesia is one of the countries currently developing the concept of halal tourism. Halal tourism includes many variables that are related to each other, which need to be grouped into several main factors that affect tourist visits. This study was conducted to group the variables associated with halal tourism visits to Lombok Island using factor analysis and to classify sub-districts and halal tourism destinations on Lombok Island using the Plaid Bicluster algorithm. Based on the analysis using the main component extraction technique in factor analysis with varimax rotation, it can be concluded that the 9 halal tourism characteristic variables can be grouped into 2 main factors. Furthermore, by using the Plaid Bicluster algorithm, 2 Bicluster were produced. There were 7 sub-districts and 9 destinations formed in Bicluster I, and 8 sub-districts and 3 destinations formed in Bicluster II.